Empowering higher education through a micro-credential program in power electronics course - Norazila, Jaalam; Mohd Shafie, Bakar; Abu Zaharin, Ahmad; Suliana, Ab Ghani; Norhafidzah, Mohd Saad; Nurul Wahidah, Arshad (UTM Press, 2023)
In line with the global and national shifts towards enhancing educational accessibility, flexibility, and quality, Malaysia has embarked on a transformative journey with the implementation of the Malaysian Education Blueprint 2015–2025 (Higher Education) and E-Learning Guidelines for Malaysian Higher Education Institutes. This strategic initiative acknowledges the pivotal role of e-learning in shaping the future of education by enabling greater access to knowledge and skills. The COVID-19 pandemic has further accelerated the growth of e-learning, emphasizing the need for innovative educational approaches. This paper presents a micro-credential program in the field of power electronics, aligned with Malaysia's commitment to advancing higher education through technology-driven solutions. The curriculum, which is tailored to meet the needs of a wide range of learners, covers all the fundamentals of power electronics and leaves participants with specific knowledge and abilities. This micro-credential program is designed to empower professionals and students, supporting their career objectives in the dynamic power electronics industry, by emphasizing accessibility, flexibility, and high-quality learning experiences.